Effect of Velocity Anisotropy in Shale on the Acoustic Emission Events Matching and Location - Wang, Peng; Zhang, Feng; Li, Xiang-Yang (Frontiers in Earth Science, 2022)
The exact location of the source of the event is important for monitoring and characterizing the fracture. The anisotropy of velocity has a great influence on both matchings of events and their location. Failure to take into account the velocity anisotropy can lead to huge errors in locating events. In this article, we have presented an experimental study on a sample of the lower Silurian shale from the Sichuan Basin. Experimental observations include ultrasonic measurements, acoustic emissions (AEs) in a three-point bend experiment, and CT of the original specimen and the fractured specimen. Ultrasonic measurements show that the shale sample has strong velocity anisotropy. Initially, AEs are analyzed using conventional event matching method and event location method (Geiger’s method), and the detected events are compared to the X-ray image of the fracture. Event matching aims to obtain AE signals from the same event source, and thus assist in selecting valid AE signals that come from the same source and are received by at least four sensors, to determine the location of the source. Although many reliable signals are obtained by correlating isotropic events, fewer sources were found than expected, and the event location results did not match the fracture distribution. To address this problem, an improved event matching method is proposed using a stricter matching threshold based on directional velocity rather than a single threshold for all directions. In addition, we propose an improved Geiger’s method using the anisotropic velocity model. The newer methods provide more localized sources that better match fracture distribution than the isotropic method. We have concluded that both event matching and the location of the shale fracture source can be highly dependent on velocity anisotropy, and thus in practice, the velocity anisotropy information obtained from various measurements (e.g. laboratory measurements, well logs, VSP and velocity analysis of reflected seismic surveys) should be involved in both processing procedures. This study will provide some background material for monitoring and predicting dynamic geo-hazards in relation to the AE (or microseismic) method.